Recurrent Migratory Transient Bone Marrow Edema of the Knees Associated with Low Vitamin D and Systemic Low Bone Mineral Density: A Case Report and Literature Review - Omar Alsaed; Mohammad Hammoudeh (Case Reports in Rheumatology)
Transient bone marrow edema (TBME) is a self-limiting disease characterized by joint pain with localized bone marrow edema by MRI and has been reported in many case series and case reports. It is well known that joints of the lower extremity including hips, knees, ankles, and feet are the classical sites for TBME. Many theories have been proposed for the pathogenesis of TBME. Systemic osteopenia and vitamin D deficiency is one of the theories that have been suggested in the last few years. In this case report, we present a middle-aged male patient, who presented with 4 attacks of TBME in both knees between September 2016 and August 2017. The patient was found to have persistently low vitamin D and osteopenic T score in DXA scan of the lumbar spine and hips. Patients of TBME usually present with joint pain that is provoked by weight-bearing physical activity. The aim of this case report is to raise the awareness that TBME can be the initial presentation of systemic loss of bone mineral density.